2009
DOI: 10.1111/j.1460-9568.2009.06811.x
|View full text |Cite
|
Sign up to set email alerts
|

A common molecular basis for membrane docking and functional priming of synaptic vesicles

Abstract: Soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE) complexes execute synaptic vesicle (SV) fusion. Vesicle fusion is preceded by an obligatory Munc13-dependent priming process that conveys fusion competence to SVs by facilitating SNARE complex assembly. Ultrastructural studies after chemical fixation indicated that vesicle docking to the plasma membrane is independent of Munc13s but these results may be misleading because aldehyde fixatives modify the localization of SVs with respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

30
166
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(209 citation statements)
references
References 33 publications
30
166
5
Order By: Relevance
“…However, at all synapses where AZM relationships have been examined by electron tomography, AZM macromolecules link the VM to the PM (2,11,12,14,27,37,(56)(57)(58)(59). This commonality, together with the high degree of homology of proteins involved in docking and priming at all synapses (60), suggests that our AZM-mediated variable force hypothesis (Fig.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…However, at all synapses where AZM relationships have been examined by electron tomography, AZM macromolecules link the VM to the PM (2,11,12,14,27,37,(56)(57)(58)(59). This commonality, together with the high degree of homology of proteins involved in docking and priming at all synapses (60), suggests that our AZM-mediated variable force hypothesis (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…At typical synapses, docking and fusion take place at structurally specialized regions along the PM called active zones (9, 10). Several lines of evidence suggest that the formation of the SNARE core complex occurs in the macromolecules composing the common active zone organelle, active zone material (AZM) (2,(11)(12)(13)(14), which is positioned near Ca 2+ channels concentrated in the PM at active zones (15-17). Influx of Ca 2+ through the channels after the arrival of a nerve impulse triggers fusion of the VM of docked SVs with the PM.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Small filaments that tether docked synaptic vesicles to the plasma membrane and to CAZ filaments have been observed by electron microscopy 105 . Cryoelectron tomography revealed that docked synaptic vesicles did not contact the active zone membrane directly but were linked to it by tethers of different lengths 106 .…”
Section: Calcium Regulationmentioning
confidence: 99%
“…Ca 2+ -dependent regulated exocytosis is generally subdivided into three processes, vesicle docking, priming, and fusion, in chronological order (19,31). Docking and priming are defined as a process that involves the physical contact between vesicles and the PM, and the subsequent formation of the trans-SNARE complex, which is ready for membrane fusion, respectively (19); however, they are thought to be closely linked processes, because a common molecular basis for their regulation has been discovered (28,34). One of the molecules that possibly regulates both docking and priming is a protein of the Munc13 family, which contains conserved domains for the assembly of the SNARE complex, and possesses membrane-binding activity (18).…”
mentioning
confidence: 99%